The Three-Ray Megacontinent of the Earth : the Fundamental Discovery of a Century. - Zhirnov, Anatoly (Cambridge Scholars Publisher, 2019)
This book explores many mysterious features of the structure and evolution of the Earth's continents, still unknown to the scientific community and a wider audience. Science has now proved that the southern continents of South America, Africa and Australia represent the southern ends of a single three-beam megacontinent. It began to form 4.4 billion years ago in a huge three-beam cavity on the planet's surface and grew vertically up to its present state. Proof of the reality of a single three-beam megacontinent is a fundamental discovery in Earth sciences, and represents a new level in the und.